Big city dreams ebook - Sztybor, Bartosz (Cyberpunk 2077 Graphic Novel, 2022)
Two scavengers in Night City make a living for themselves stealing cyberware and indulging in parties and braindances. One seeks to become the most famous gangster in the city. The other longs for something more‚Äîmeaning, belonging, warmth . . . As they chase their dreams, their paths begin to deviate. But one thing they can both agree on, in a place like Night City‚Äîyou run, you fight, you change, or you die.